2017
DOI: 10.1371/journal.pone.0183812
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1/GSTT1 double-null genotype increases risk of treatment-resistant schizophrenia: A genetic association study in Brazilian patients

Abstract: BackgroundThe role of oxidative stress in schizophrenia has been demonstrated, particularly in subjects with treatment-resistant schizophrenia (TRS). In such patients, the decreased levels of antioxidants in conjunction with the increased generation of reactive oxygen species in the brain exposes the neurons to a higher risk of damage.Methods and findingsWe evaluated the association of deletion polymorphisms of two genes of the antioxidant Glutathione S-Transferase family, GSTT1 and GSTM1, with susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
1
15
2
Order By: Relevance
“…47 In addition, Pinheiro et al showed that the double null genotype (GSTT1-null /GSTM1-null) was significantly associated with the development of SCZ; this combined genotype resulted in a 4.6-fold increased risk of developing SCZ. 48 This result was consistent with the complex genetic theory of SCZ, highlighting the effects of several genetic interactions and suggested that the combination of GST polymorphisms may play a role in susceptibility to SCZ. 49 As Milica et al said, we can understand the relationship between GST polymorphism and SCZ from the perspective of vascular injury.…”
Section: Discussionsupporting
confidence: 87%
“…47 In addition, Pinheiro et al showed that the double null genotype (GSTT1-null /GSTM1-null) was significantly associated with the development of SCZ; this combined genotype resulted in a 4.6-fold increased risk of developing SCZ. 48 This result was consistent with the complex genetic theory of SCZ, highlighting the effects of several genetic interactions and suggested that the combination of GST polymorphisms may play a role in susceptibility to SCZ. 49 As Milica et al said, we can understand the relationship between GST polymorphism and SCZ from the perspective of vascular injury.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, in this series a lower frequency of combination GSTT1-null/GSTM1-present was found in patients compared to controls, in disagreement with two meta-analyses (Kim et al, 2015;Koga et al, 2016). It is possible that the presence of one of these genotypes could attenuate the impairment caused by the absence of the other, explaining the differences in clinical profile and response to drug treatment (Pinheiro et al, 2017), which should be investigated in further studies on gene-gene and geneenvironment interactions (Hu et al, 2016).…”
Section: Discussioncontrasting
confidence: 76%
“…The prevalence of familial history of schizophrenia adds relevance to genetic factors for the disease (Pinheiro et al, 2017). In this context, the association of the GSTM1 genotype in East Asian patients with schizophrenia, but not for GSTT1 (Kim et al, 2015) is emphasized, whereas in our study the genotypes of the two polymorphisms were similar between the groups.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations